The Role of Internal Auditors in Implementation Social Environmental Governance - Ramadhan, Yanuar; Ramzy, Wahyu; Munawaroh, Faridatul; Sunardi, Dadi (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
The aim of this study is to know how big the role of the auditor is in raising awareness of the application of sustainability reporting and the extent to which information is disclosed on the aspects of Environment, Social and Governance (ESG). Several previous studies were used as objects reviewed. The result underscores the multifaceted contributions of internal auditors, ranging from providing assurance on ESG disclosures and conducting due diligence on business partners to engaging in consulting activities and fostering a sustainable supply chain. This practice emphasizes that ESG-related expertise within Internal Audit Functions (IAFs) is crucial for promoting ESG maturity and effective reporting. Collaboration between internal and external auditors is vital to maintain independence and objectivity, ensuring the quality and reliability of ESG-related information. The trend of integrating ESG considerations into audit processes aligns with the broader global shift toward responsible business practices, and it positions internal auditors as valuable contributors to corporate governance and stakeholder trust. As ESG gains prominence, the internal auditor's ability to navigate the complexities of ESG metrics and controls becomes a competitive advantage, reinforcing their role as a key player in achieving sustainable and responsible business outcomes.